2016
DOI: 10.1111/liv.13110
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline phosphatase at diagnosis of primary sclerosing cholangitis and 1 year later: evaluation of prognostic value

Abstract: ALP can be used to discriminate between PSC patients with a good and a poor prognosis. These findings indicate that ALP can serve as stratifier, and potentially as surrogate endpoint for clinical trials in PSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 23 publications
3
67
0
Order By: Relevance
“…Endpoints were PSC‐related death or LT. Using a systematic approach to distinguish patients with a more favorable versus poor outcome yielded a positive association between level of ALP both at diagnosis and at 1 year, and the hazard of reaching an endpoint was around 2.5 × ULN . A larger decrease in ALP in the first year after diagnosis decreased the event rate.…”
Section: Potential Biomarkersmentioning
confidence: 99%
“…Endpoints were PSC‐related death or LT. Using a systematic approach to distinguish patients with a more favorable versus poor outcome yielded a positive association between level of ALP both at diagnosis and at 1 year, and the hazard of reaching an endpoint was around 2.5 × ULN . A larger decrease in ALP in the first year after diagnosis decreased the event rate.…”
Section: Potential Biomarkersmentioning
confidence: 99%
“…For example, SAP was lower in those with ED PSC and tended to remain <1.5× the ULN years after the initial diagnosis. A lower SAP has been associated with an improved prognosis . In addition, their MELD score was significantly lower at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 97%
“…Four to fourteen percent of patients with PSC will have overlapping autoimmune hepatitis (AIH) (4, 6, 26). There remains controversy and a lack of consensus on the criteria that should be used to define PSC-AIH overlap, which may appear simultaneously or PSC may appear following a diagnosis of AIH.…”
Section: Introductionmentioning
confidence: 99%
“…The elevated laboratory values may decrease after the diagnosis, as one study with over 300 patients showed that the average alkaline phosphatase, aspartate transaminase, alanine transaminase, and total bilirubin decreased from 1.99, 1.45, 2.11, 0.81 x the upper limit of normal to 1.22, 0.88, 1.00, and 0.65 x the upper limits of normal in one year (26). In fact, up to 40% of patients may experience normalized alkaline phosphatase levels in 1 year, and these patients have a higher rate of liver transplant-free survival (26, 38). Hepatomegaly and splenomegaly are present in 43.6% and 29.3% of patients, respectively, at presentation (9).…”
Section: Introductionmentioning
confidence: 99%